Mayors and money : fiscal policy in New York and Chicago - Fuchs, Ester R., 1951- (American politics and political economy., 1992)
Chicago and New York share similar backgrounds but have had strikingly different fates. Tracing their fortunes from the 1930s to the present day, Ester R. Fuchs examines key policy decisions which have influenced the political structures of these cities and guided them into, or clear of, periods of economic crisis.